2014
DOI: 10.1111/1574-6968.12359
|View full text |Cite
|
Sign up to set email alerts
|

VOC emission of variousSerratiaspecies and isolates and genome analysis ofSerratia plymuthica4Rx13

Abstract: Bacteria emit a wealth of volatile organic compounds. Gas chromatography coupled to mass spectrometry analysis of five Serratia strains revealed ketones, dimethyl di- and trisulfide and 2-phenylethanol commonly released in this genus. The polymethylated bicyclic hydrocarbon sodorifen was uniquely released by the rhizobacterium Serratia plymuthica 4Rx13. Of 10 Serratia strains, only S. plymuthica isolates originating from plants grown on fields near Rostock (Germany) released this new and unusual compound. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 50 publications
0
34
0
3
Order By: Relevance
“…As well as commonly known bacterial VOCs such as 2-pentanone, 4-heptanone, 2-heptanol, 2-undecanone, 2-tridecanone, and 2-pentadecanone (Schulz and Dickschat, 2007; Weise et al, 2014), well known compounds like sodorifen, a bicyclic oligomethyl octadiene produced by Serratia odorifera (Kai et al, 2010), are able to interfere with plants ( Figure 2 ).…”
Section: Overview Of Bioactive Bacterial Volatilesmentioning
confidence: 99%
“…As well as commonly known bacterial VOCs such as 2-pentanone, 4-heptanone, 2-heptanol, 2-undecanone, 2-tridecanone, and 2-pentadecanone (Schulz and Dickschat, 2007; Weise et al, 2014), well known compounds like sodorifen, a bicyclic oligomethyl octadiene produced by Serratia odorifera (Kai et al, 2010), are able to interfere with plants ( Figure 2 ).…”
Section: Overview Of Bioactive Bacterial Volatilesmentioning
confidence: 99%
“…Scrutiny of the genome also revealed the presence of a biosynthetic cluster responsible for production of the antifungal metabolite pyrrolnitrin (12). Genome comparison analyses showed that the genome of 4Rx5 is highly similar to that of Serratia plymuthica 4Rx13 (13). The strain 4Rx13 produces a broad range of volatile organic compounds (VOCs) (1315), some of them possessing antifungal properties (14).…”
Section: Announcementmentioning
confidence: 99%
“…Genome comparison analyses showed that the genome of 4Rx5 is highly similar to that of Serratia plymuthica 4Rx13 (13). The strain 4Rx13 produces a broad range of volatile organic compounds (VOCs) (1315), some of them possessing antifungal properties (14). The bicyclic terpene sodorifen was the major VOC emitted by 4Rx13 (15), and the sodorifen gene cluster was identified in the genome of 4Rx5.…”
Section: Announcementmentioning
confidence: 99%
“…Estos resultados coinciden con los obtenidos por Queiroz y De Melo (2006), quienes reportaron que S. marcescens posee el mayor grado de antagonismo in vitro al inhibir el crecimiento micelial de P. parasitica; además tiene la capacidad de reducir en 50 % la infección de este patógeno, inducir el crecimiento de las plantas y suprimir a P. parasitica en condiciones de campo en plántulas de cítricos. S. plymuthica, es otra especie con potencial para uso en biocontrol (Weise et al, 2014).…”
Section: Identificación De Bacterias Antagonistasunclassified